2006
DOI: 10.1016/j.jcomdis.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Relation of emotional reactivity and regulation to childhood stuttering

Abstract: The purpose of the present study was to examine relations between children's emotional reactivity, emotion regulation and stuttering. Participants were 65 preschool children who stutter (CWS) and 56 preschool children who do not stutter (CWNS). Parents completed the Behavior Style Questionnaire (BSQ) [McDevitt S. C., & Carey, W. B. (1978). A measure of temperament in 3-7 year old children. Journal of Child Psychology and Psychiatry and Allied Disciplines,19,[245][246][247][248][249][250][251][252][253]. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
193
6
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 173 publications
(229 citation statements)
references
References 59 publications
(74 reference statements)
26
193
6
2
Order By: Relevance
“…Findings complement others in suggesting differences in specific aspects of temperament (e.g., emotion reactivity, emotion regulation, attention regulation, behavioral inhibition) between children who stutter (CWS) and children who do not stutter (CWNS) or differences among sub-groups of CWS based on age or other characteristics of stuttering (e.g., disfluency type, presence of secondary behaviors) [1,[7][8][9][10][11]. However, a systematic review of the literature suggests that not all children who stutter present with temperamental characteristics of high reactivity and inattention and may just affect a sub-group of children who stutter [1].…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Findings complement others in suggesting differences in specific aspects of temperament (e.g., emotion reactivity, emotion regulation, attention regulation, behavioral inhibition) between children who stutter (CWS) and children who do not stutter (CWNS) or differences among sub-groups of CWS based on age or other characteristics of stuttering (e.g., disfluency type, presence of secondary behaviors) [1,[7][8][9][10][11]. However, a systematic review of the literature suggests that not all children who stutter present with temperamental characteristics of high reactivity and inattention and may just affect a sub-group of children who stutter [1].…”
Section: Introductionsupporting
confidence: 57%
“…Karrass et al also employed the BSQ to investigate temperamental differences in young CWS and CWNS ages 3-5 years of age in comparison to their typically fluent peers [11]. This study found that parents of CWS reported their children to have higher emotional reactivity and less emotional regulation in comparison to parentreports of CWNS.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations